2013
DOI: 10.1021/jp4012558
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Generation by Laser Irradiation of Carbon Powder in Water

Abstract: We report the photochemical activity of carbon powder in the generation of hydrogen from water by laser irradiation, without any electrodes and photocatalysts. The gas was obtained by laser irradiation in the VIS-NIR range and was dependent nonlinearly on the laser power density. From a gas component analysis and a repeated irradiation experiment, it was found that the carbon powder was oxidized and acted as a sacrificial reagent in the photochemical hydrogen generation. In addition, a highly carbonized charco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Some follow-up studies of this process have been reported by Dubey et al [13] using a carbon nanotube anode and by Giddy et al [14] using a solid-state electrolytic cell. A different variation of this process involving hydrogen generation by laser irradiation of a carbon powder suspension in water has been reported by Akimoto et al [15]. Results of the hydrogen evolution rate R H using a variety of carbons show some proportionality to the surface area of a carbon which in turn is related to the pore structure of the carbons.…”
Section: Introductionmentioning
confidence: 82%
“…Some follow-up studies of this process have been reported by Dubey et al [13] using a carbon nanotube anode and by Giddy et al [14] using a solid-state electrolytic cell. A different variation of this process involving hydrogen generation by laser irradiation of a carbon powder suspension in water has been reported by Akimoto et al [15]. Results of the hydrogen evolution rate R H using a variety of carbons show some proportionality to the surface area of a carbon which in turn is related to the pore structure of the carbons.…”
Section: Introductionmentioning
confidence: 82%
“…Hydrogen is provided by the laser dissociation of water molecules coming both from dehydration of the gypsum surface and from the water sprayed by the operator before the laser cleaning. Indeed, in presence of nanoparticles, water radiolysis and breakdown are caused by the secondary electrons flux generated by the visible/IR laser irradiations [32,33]. Water dissociation also provides O and OH radicals allowing for oxidation and hydroxylation of the carbon precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary tests on the ablation of a steel target in water confirm this hypothesis. In this point of view the results of previous work on hydrogen emission under laser exposure of carbon particles in water [5] could be re-considered. Indeed, the laser fluence used in this work was of order of 100 mJ/cm 2 is not sufficient for water breakdown.…”
Section: Discussionmentioning
confidence: 99%